FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PELAKSANAAN INISIASI MENYUSU DINI (IMD) PADA IBU POST PARTUM DI RUANG BERSALIN RUMAH SAKIT YARSI PONTIANAK - Yasita, Nova; Taufik, M; Trisnawati, Elly (JUMANTIK (Jurnal Mahasiswa dan Peneliti Kesehatan), 2014)
Early Initiation of Breastfeeding (IMD) is one way to lower the infant mortality rate (IMR). Early Initiation of Breastfeeding Practice (IMD), especially in Indonesia is still very low. Early Initiation of Breastfeeding is giving breast milk to newborns, infants should not be cleaned in advance and are not separated from the mother. Early Initiation of Breastfeeding Success program (IMD) is also strongly influenced by the attitudes, knowledge and methods of delivery and physical fatigue experienced by mothers giving birth. This study aims to determine the factors associated with the implementation of early breastfeeding initiation (IMD) in women post partum in Hospital Delivery Room Yarsi Pontianak. This research is an analytic survey with cross sectional approach. Large sample study of 56 samples. Each of the studied variables were tested using Chi-square test. The results show that knowledge (p value = 0.034), attitude (p value = 0.008), method of delivery (p value = 0.016), physical fatigue (p value =0.01), and family support (husband) (p value = 0.007) had a significant relationship with the implementation of the IMD on Post Partum Mother in Hospital Delivery Room Yarsi Pontianak. Advice for hospitals to cooperate with midwives in private practice and community health centers to provide an explanation about the meaning and importance of IMD.Keywords : Knowledge , Attitude , Method of Delivery , Physical Fatigue ,Family Support , Early Initiation of Breastfeeding ( IMD )